Strategies to increase patient loyalty through the implementation of terra service quality - Irsal Fauzi; Sudiyono; Ignatius Bias Galih Prasadhya (International Journal of Applied Finance and Business Studies, 2023)
The purpose of this study is to examine the effect of TERRA service quality, and its impact on loyalty, and its implementation based on the theory of planned behavior. The reason why researchers chose service quality measured using the TERRA Formulation is because the TERRA Formulation is very easy to implement at a practical level, and can more accurately measure the needs of companies in the field, compared to other service quality formulations. This type of research is quantitative, with the main data source in the form of a questionnaire, which will be analyzed using SEM PLS. the formation of the service process, which will increase the loyalty index measured by the TERRA service quality dimensions. The results showed that Tangibel, Emphaty, Reliability, Responsiveness and Assurance have a positive effect on Loyalty. From the results of the analysis, it can be concluded that there are positive results between the dimensions of TERRA service quality on loyalty, and the dimensions of TERRA service quality are able to confirm the theory of planned behavior that has an impact on loyalty.